Phosphorus-carbon composite negative electrode material and preparation method thereof, negative electrode plate and secondary battery

By combining porous carbon materials with phosphorus elemental materials, a phosphorus-carbon composite negative electrode material with irregular pore structures and regular pore structures is prepared, which solves the problems of low material capacity, poor conductivity and poor circulation performance in the prior art, and achieves efficient battery performance improvement.

CN119905556APending Publication Date: 2025-04-29SODIUM TECHNOLOGY CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510011133.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, phosphorus-carbon composite anode material has problems such as low capacity, poor electronic conductivity, high expansion rate and poor circulation performance in battery applications.

Method used

By combining porous carbon materials with phosphorus elemental substances (red phosphorus or black phosphorus), high-temperature sintering and heat treatment are used to prepare phosphorus-carbon composite negative electrode materials to form irregular pore structures and regular pore structures to improve the electrochemical performance of the material.

Benefits of technology

The performance of negative electrode material with high magnification, low expansion, high capacity and long cycles is achieved, and the rate performance, energy density and cycle performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905556A_ABST
    Figure CN119905556A_ABST
Patent Text Reader

Abstract

The invention relates to a phosphorus-carbon composite negative electrode material, which comprises: a porous carbon material; the porous carbon material has an irregular pore channel structure and a regular pore structure; the irregular pore structures are through holes or closed holes, the pore diameter of more than 99% of the irregular pore structures is less than 2nm, and the pore diameter of less than 1% of the irregular pore structures is greater than 2nm; the regular hole structure is a through hole, and the hole diameter of the regular hole structure is in a nanometer level or a micrometer level; elemental phosphorus is arranged in the irregular pore channel structure and the regular pore structure; the phosphorus elementary substance is a red phosphorus elementary substance or a black phosphorus elementary substance. According to the preparation method, the problems of low material capacity and the like caused by small volume constraint effect and less depositable phosphorus when simple substance phosphorus is deposited in a pure porous carbon structure are effectively solved, and the high-rate, low-expansion, high-capacity and long-cycle negative electrode material can be obtained, so that the rate capability, the energy density and the cycle performance of the battery are improved to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a phosphorus-carbon composite negative electrode material and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art

[0002] In the current field of battery technology, with the growing demand for high energy density and safety, the development of anode materials has become particularly important. Hard carbon, red phosphorus, and black phosphorus, as potential anode materials, have attracted widespread attention due to their unique physical and chemical properties.

[0003] As a carbon negative electrode material, hard carbon exhibits good electrochemical performance due to its excellent microstructural characteristics, such as highly disordered carbon atom arrangement, large interlayer spacing and adjustable pore structure. Its reversible capacity is usually less than 350mAh / g. The raw materials of hard carbon come from a wide range of sources, including biomass, resin, coal, and minerals such as petroleum coke, and its cost is low, which provides broad prospects for its application in the field of batteries. However, the gram capacity of hard carbon is low, which makes it difficult to meet the needs of high energy density battery cell design. At the same time, due to the influence of material structure and carbon atom arrangement, its compaction density is too low and its electronic conductivity is poor.

[0004] Red phosphorus has a high theoretical capacity (2596 mAh g -1 ) negative electrode material, its redox potential is relatively safe (0.4V-Na / Na + ), which can avoid the formation of sodium dendrites during the charge and discharge process, thereby reducing safety hazards. Red phosphorus can be used as a negative electrode material for sodium batteries, but its conductivity is low (about 10 -12 S·m -1 ), and is accompanied by large volume changes during the charge and discharge process, resulting in low Coulombic efficiency and rapid capacity decay.

[0005] Black phosphorus is known for its wrinkled lamellar structure, high electrical conductivity (about 10 2 S·m -1 ) and an adjustable bandgap structure make it one of the negative electrode materials for sodium ion batteries with high capacity, high conductivity and low expansion. However, the preparation of black phosphorus has strict environmental requirements and high cost, which limits its wide application in the battery field.

[0006] Therefore, there is an urgent need for a phosphorus-carbon composite negative electrode material and a preparation method thereof, a negative electrode plate and a secondary battery. Summary of the invention

[0007] The purpose of the present invention is to provide a phosphorus-carbon composite negative electrode material and a preparation method thereof, a negative electrode plate and a secondary battery in view of the deficiencies in the prior art.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention is to provide a phosphorus-carbon composite negative electrode material, comprising: a porous carbon material;

[0010] The porous carbon material has an irregular pore structure and a regular pore structure;

[0011] Wherein, the irregular pore structure is a through hole or a closed hole, more than 99% of the irregular pore structure has a pore size less than 2nm, and less than 1% of the irregular pore structure has a pore size greater than 2nm;

[0012] Wherein, the regular hole structure is a through hole, and the pore size of the regular hole structure is nanometer-scale or micrometer-scale;

[0013] Wherein, the irregular pore structure and the regular pore structure contain phosphorus;

[0014] Wherein, the phosphorus element is red phosphorus element or black phosphorus element.

[0015] The second aspect of the present invention is to provide a method for preparing the phosphorus-carbon composite negative electrode material as described above, the steps comprising:

[0016] S1, mixing an excess of carbon material, phosphate, and silicon dioxide, and sintering at high temperature so that the carbon material, the phosphate, and the silicon dioxide react to generate carbon monoxide gas, phosphorus vapor, and silicate, and then cooling to obtain a first mixture;

[0017] Wherein, the excess carbon material partially reacts to generate the carbon monoxide gas to form an irregular pore structure on the remaining carbon material;

[0018] The phosphorus vapor generated by the reaction solidifies into phosphorus element during the cooling process and is mixed with the remaining carbon material and the silicate generated by the reaction to obtain the first mixture;

[0019] S2, heat-treating the first mixture to obtain a second mixture;

[0020] Wherein, the phosphorus element is transformed into red phosphorus element or black phosphorus element by heat;

[0021] S3, stirring the second mixture in dilute acid to obtain a third mixture;

[0022] wherein the silicate is dissolved by the dilute acid to form a regular pore structure on the carbon material;

[0023] S4, sequentially performing a pulverization process and a demagnetization process on the third mixture to obtain the phosphorus-carbon composite negative electrode material.

[0024] Preferably, the carbon material is selected from at least one of graphite, hard carbon, soft carbon, or mesophase carbon microspheres;

[0025] Wherein, the hard carbon is selected from at least one of biomass hard carbon, resin hard carbon, coal-based hard carbon, or petroleum coke / needle coke-based hard carbon.

[0026] Preferably, the high-temperature sintering is performed under an inert atmosphere, the temperature of the high-temperature sintering is 1300° C.-1600° C., and the time of the high-temperature sintering is 1 h-4 h.

[0027] Preferably, the phosphorus element, the carbon material, and the silicate are further mixed under an inert atmosphere, and the further mixing is at least one of VC mixing, high-speed mixing, or ball milling mixing.

[0028] Preferably, the heat treatment is performed under an inert atmosphere, the heat treatment temperature is 200° C.-600° C., and the heat treatment time is 2 h-8 h.

[0029] Preferably, the second mixture is stirred in the dilute acid for 2 h to 10 h, the dilute acid is dilute nitric acid or / and dilute hydrochloric acid, and the concentration of the dilute acid is 1% to 10%.

[0030] Preferably, after the pulverization process, the average particle size D50 of the particles is 5 μm-6 μm.

[0031] The second aspect of the present invention is to provide a negative electrode plate, comprising: the phosphorus-carbon composite negative electrode material as described above.

[0032] A third aspect of the present invention is a secondary battery, comprising: the negative electrode sheet as described above.

[0033] Preferably, the secondary battery is a sodium ion secondary battery.

[0034] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0035] In the preparation method of the present invention, the ratio of carbon material, phosphate and silicon dioxide can regulate the ratio of irregular pore structure, the cooling rate during cooling can regulate the ratio of regular pore structure, and the mixing method of phosphorus element, carbon material and silicate can regulate the morphology of phosphorus-carbon composite negative electrode material; thereby effectively solving the problems of small volume constraint effect when depositing elemental phosphorus in a simple porous carbon structure, less depositable phosphorus resulting in lower material capacity, etc., and a negative electrode material with high rate, low expansion, high capacity and long cycle can be obtained, thereby improving the rate performance, energy density and cycle performance of the battery to a certain extent, and bringing significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the structure of the phosphorus-carbon composite negative electrode material in the present invention;

[0037] Figure 2 This is a graph showing the electron microscopy results in Comparative Example 1 of the present invention;

[0038] Figure 3 This is a graph showing the electron microscopy results in Comparative Example 3 of the present invention;

[0039] Figure 4 This is a schematic diagram of the structure of the phosphorus-carbon composite negative electrode material in Comparative Example 5 of the present invention;

[0040] Figure 5 This is a graph showing the electron microscopy results in Example 1 of the present invention;

[0041] Figure 6 The first cycle charge and discharge curves of Example 1 and Example 2 of the present invention;

[0042] Figure 7 Schematic diagram of the structure of the phosphorus-carbon composite negative electrode material in Example 4 of the present invention;

[0043] Figure 8 This is a graph showing the electron microscopy results in Example 9 of the present invention;

[0044] The reference numerals include:

[0045] Porous carbon material 1; irregular pore structure 11; regular pore structure 12; phosphorus element 2. DETAILED DESCRIPTION

[0046] The specific embodiments of the present invention will be described in detail below.

[0047] Unless otherwise defined, technical or scientific terms used in the claims and the specification shall have the common meanings understood by persons having ordinary skills in the technical field to which the present invention belongs.

[0048] The words "include" or similar words used in the patent application specification and claims of the present invention mean that the items appearing before "include" include the items listed after "include" or their equivalents, and do not exclude other items.

[0049] The numerical values ​​mentioned in the present invention include all numerical values ​​that increase from low to high by one unit, assuming that there are at least two units between any lower value and the higher value. For example, if a component or a physical quantity is said to be from 1 to 100, 10 to 90 is more preferred, and 20 to 80 is the most preferred, it is intended to express that values ​​such as 5 to 95, 14 to 76, 23 to 67, 32 to 58, 41 to 49 are clearly listed in this specification; for values ​​less than 1, 0.0001, 0.001, 0.01 or 0.1 are considered to be more suitable as a unit. The above examples are for illustrative purposes only. In fact, all numerical combinations between the lowest value and the highest value listed are deemed to be clearly listed in this specification in a similar manner.

[0050] The embodiment of the present invention first provides a phosphorus-carbon composite negative electrode material, such as Figure 1 As shown, it includes: a porous carbon material 1;

[0051] The porous carbon material 1 has an irregular pore structure 11 and a regular pore structure 12;

[0052] The irregular pore structure 11 is a through hole or a closed hole, more than 99% of the irregular pore structure 11 has a pore size less than 2 nm, and less than 1% of the irregular pore structure 11 has a pore size greater than 2 nm;

[0053] Wherein, the regular hole structure 12 is a through hole, and the pore size of the regular hole structure 12 is nanometer-level or micrometer-level;

[0054] The irregular pore structure 11 and the regular pore structure 12 contain phosphorus element 2;

[0055] Wherein, the phosphorus element 2 is red phosphorus element or black phosphorus element.

[0056] The embodiment of the present invention further provides a method for preparing the phosphorus-carbon composite negative electrode material as described above, the steps comprising:

[0057] S1. After mixing excess carbon material, phosphate, and silicon dioxide, sintering is performed at high temperature (1300° C.-1600° C., 1 h-4 h) under an inert atmosphere, so that the carbon material, the phosphate, and the silicon dioxide react to generate carbon monoxide gas, phosphorus vapor, and silicate:

[0058] 10C+4PO4 3- +6SiO2→10CO+P4+6SiO3 2-

[0059] Wherein, the excess carbon material partially reacts to generate the carbon monoxide gas to form an irregular pore structure on the remaining carbon material;

[0060] Then, the temperature is lowered to 25°C at a rate of 1°C / min-10°C / min, and the phosphorus vapor generated by the reaction solidifies into phosphorus element during the cooling process;

[0061] The phosphorus element, the remaining carbon material, and the silicate generated by the reaction are further mixed under an inert atmosphere to obtain a first mixture;

[0062] S2, heat-treating the first mixture under an inert atmosphere (200° C.-600° C., 2 h-8 h) to obtain a second mixture;

[0063] Wherein, the phosphorus element is transformed into red phosphorus element or black phosphorus element by heat;

[0064] S3, stirring the second mixture in a dilute acid with a concentration of 1% to 10% for 2 hours to 10 hours to obtain a third mixture;

[0065] wherein the silicate is dissolved by the dilute acid to form a regular pore structure on the carbon material;

[0066] S4, successively pulverizing the third mixture until the average particle size D50 of the particles is 5 μm-6 μm, and performing a demagnetization treatment to obtain the phosphorus-carbon composite negative electrode material.

[0067] Specifically, the carbon material is selected from at least one of graphite, hard carbon, soft carbon, or mesophase carbon microspheres.

[0068] More specifically, the hard carbon is selected from at least one of biomass hard carbon, resin hard carbon, coal-based hard carbon, and petroleum coke / needle coke-based hard carbon.

[0069] Specifically, the further mixing is at least one of VC mixing, high-speed mixing, or ball milling mixing.

[0070] Specifically, the dilute acid is dilute nitric acid and / or dilute hydrochloric acid.

[0071] Finally, an embodiment of the present invention provides a negative electrode sheet, comprising: a negative electrode current collector, and a negative electrode active material layer coated on the surface of the negative electrode current collector; wherein:

[0072] The negative electrode active material layer comprises: the phosphorus-carbon composite negative electrode material as mentioned above, a negative electrode conductor, and a negative electrode binder.

[0073] Those skilled in the art can understand that the function of the negative electrode current collector is to collect current, and the material of the negative electrode current collector can be any material suitable for a negative electrode current collector of a sodium ion battery in the art, for example: metal foil, more specifically, aluminum foil; the negative electrode conductive agent can be any material suitable for a negative electrode conductive agent of a sodium ion battery in the art, for example: carbon black (for example: Super-P, or / and KS-6), VGCF, multi-walled carbon nanotubes (CNT), or at least one of single-walled carbon nanotubes; the negative electrode binder can be any material suitable for a negative electrode binder of a sodium ion battery in the art, for example: at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyimide (PI), polyacrylonitrile (PAN), or polyvinylidene fluoride (PVDF).

[0074] The steps for preparing the negative electrode sheet provided in the embodiment of the present invention include:

[0075] The phosphorus-carbon composite negative electrode material, negative electrode conductive agent, and negative electrode adhesive as described above are mixed into a slurry in a mass ratio of (90-99): (0.05-5): (0.5-5), the slurry is applied to the surface of the negative electrode collector, and the negative electrode collector coated with the slurry is rolled and die-cut in sequence to obtain the negative electrode.

[0076] Similarly, an embodiment of the present invention provides a secondary battery, comprising: a negative electrode sheet, a positive electrode sheet, and a separator as described above; wherein:

[0077] A plurality of the negative electrode sheets and a plurality of the positive electrode sheets are stacked in sequence, and the separator is arranged between adjacent negative electrode sheets and positive electrode sheets;

[0078] The positive electrode sheet comprises: a positive electrode current collector, and a positive electrode active material layer coated on the surface of the positive electrode current collector;

[0079] The positive electrode active material layer includes a positive electrode active material, a positive electrode conductor, and a positive electrode binder.

[0080] It can be understood by those skilled in the art that the separator can be any material suitable for sodium ion battery separators in the art, for example, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, or at least one of natural fibers; the positive electrode collector can be any material suitable for sodium ion battery positive electrode collector in the art, for example, metal foil, more specifically, aluminum foil; the positive electrode active material can be any material suitable for sodium ion battery positive electrode active material in the art, for example, at least one of layered transition metal sodium oxide, polyanion positive electrode material, or Prussian positive electrode material, the layered transition metal sodium oxide The material can also be doped with elements such as Li, Mg, Zn, Ca, Al, V, Cr, Mn, Fe, Ti, Zr, Sn, Ru, Nb, Co, or Ni; the positive electrode conductor can be any material suitable for positive electrode conductors of sodium ion batteries in the art, for example, at least one of carbon black (for example, Super-P and / or KS-6), VGCF, multi-walled carbon nanotubes (CNT), or single-walled carbon nanotubes; the positive electrode binder can be any material suitable for positive electrode binders of sodium ion batteries in the art, for example, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyimide (PI), polyacrylonitrile (PAN), or polyvinylidene fluoride (PVDF).

[0081] The "hard carbon" mentioned in the comparative examples or embodiments of the present invention all uses coconut shells, but those skilled in the art can use other biomass raw materials, or similar hard carbon materials, and the corresponding technical effects can be reasonably expected;

[0082] The "soft carbon" mentioned in the comparative examples or embodiments of the present invention all uses asphalt, but those skilled in the art can use other mineral raw materials, or similar soft carbon materials, and the corresponding technical effects can be reasonably expected;

[0083] In order to verify the performance of the embodiments or comparative examples described later, the present invention directly uses sodium foil as the positive electrode to assemble a sodium ion secondary battery for verification, and except for the negative electrode material, the materials selected in the sodium ion secondary batteries for verification of each embodiment and comparative example are the same.

[0084] Comparative Example 1

[0085] This comparative example provides a phosphorus-carbon negative electrode material, the preparation steps of which include:

[0086] S1, directly mixing hard carbon and red phosphorus in a molar ratio of 20:1 under an inert atmosphere to obtain a first mixture;

[0087] S2, the first mixture is crushed in turn until the average particle size D50 of the particles is 5 μm-6 μm, and then subjected to demagnetization treatment, so as to obtain the phosphorus-carbon negative electrode material, and the electron microscopy characterization is as follows: Figure 2 shown.

[0088] Comparative Example 2

[0089] This comparative example provides a phosphorus-carbon negative electrode material, the preparation steps of which include:

[0090] S1, directly mixing hard carbon and black phosphorus in a molar ratio of 20:1 under an inert atmosphere to obtain a first mixture;

[0091] S2, successively pulverizing the first mixture until the average particle size D50 of the particles is 5 μm-6 μm, and performing a demagnetization treatment to obtain the phosphorus-carbon negative electrode material.

[0092] Compared with Comparative Example 1, the black phosphorus in Comparative Example 2 has higher conductivity, so the internal resistance of the battery made of phosphorus-carbon negative electrode material is lower; at the same time, black phosphorus has a layered structure, and its volume changes little during the insertion and extraction of sodium, so the battery cycle performance is slightly better than that of Comparative Example 1.

[0093] Comparative Example 3

[0094] This comparative example provides a phosphorus-carbon composite negative electrode material, the preparation steps of which include:

[0095] S1, mixing hard carbon and white phosphorus in a molar ratio of 20:1 under an inert atmosphere to obtain a first mixture;

[0096] S2, heat treating the first mixture under an inert atmosphere (300° C., 6 h) to obtain a second mixture;

[0097] Wherein, the white phosphorus element is transformed into red phosphorus element by heating;

[0098] S3, the second mixture is successively pulverized until the average particle size D50 of the particles is 5 μm-6 μm, and then subjected to demagnetization treatment, so as to obtain the phosphorus-carbon composite negative electrode material, and the electron microscopy characterization is as follows: Figure 3 shown.

[0099] In comparative example 3, the white phosphorus element undergoes a structural transformation under high temperature conditions by heat treatment, and is in-situ attached to the surface of the hard carbon. Compared with the product directly mixed in comparative example 1, the two are basically equal in capacity and cycle performance;

[0100] In addition, since phosphorus undergoes a large volume change during the insertion and extraction process of sodium, the cycle stability of Comparative Examples 1 and 3 is poor.

[0101] Comparative Example 4

[0102] This comparative example provides a phosphorus-carbon composite negative electrode material, the preparation steps of which include:

[0103] S1, mixing hard carbon and white phosphorus in a molar ratio of 20:1 under an inert atmosphere to obtain a first mixture;

[0104] S2, heat-treating the first mixture under an inert atmosphere (1.5 GPa, 200° C., 6 h) to obtain a second mixture;

[0105] Wherein, the white phosphorus element is transformed into black phosphorus element by heating;

[0106] S3, successively pulverizing the second mixture until the average particle size D50 of the particles is 5 μm-6 μm, and performing a demagnetization treatment to obtain the phosphorus-carbon composite negative electrode material.

[0107] Comparative Example 4 uses heat treatment to make the white phosphorus undergo structural transformation under high temperature conditions and adhere to the surface of hard carbon in situ. Compared with the product directly mixed in Comparative Example 2, the two are basically the same in capacity and cycle performance;

[0108] As mentioned above, compared with Comparative Example 3, Comparative Example 4 has lower internal resistance and better rate performance.

[0109] Comparative Example 5

[0110] This comparative example provides a phosphorus-carbon composite negative electrode material, and its preparation steps are as shown in Example 1 of the prior art CN118289757A.

[0111] like Figure 4 As shown, in the phosphorus-carbon composite negative electrode material of this comparative example, a porous structure is formed on the surface of the hard carbon material, and a closed-pore structure is formed inside, and the phosphorus element is located in the porous structure; however, the pore size of the porous structure is small, so the storage capacity for the phosphorus element is less and the space provided for the expansion of the phosphorus element is smaller, so the capacity and cycle performance are poor.

[0112] Example 1

[0113] This embodiment provides a phosphorus-carbon composite negative electrode material, the preparation steps of which include:

[0114] S1. Mix hard carbon, calcium phosphate, and silicon dioxide in a molar ratio of 20:1:3, and sinter at high temperature under an inert atmosphere (dynamic rotary kiln, 1400°C, 3h):

[0115] 10C+2Ca3(PO4)2+6SiO2→10CO+P4+6CaSiO3

[0116] The carbon monoxide gas generated by the reaction overflows to form an irregular pore structure on the hard carbon that has not reacted completely;

[0117] Then, the temperature is lowered to 25° C. at a rate of 10° C. / min, and the phosphorus vapor generated by the reaction solidifies into phosphorus element during the cooling process;

[0118] The phosphorus element, the hard carbon, and the calcium silicate generated by the reaction are further mixed under an inert atmosphere (VC mixer) to obtain a first mixture;

[0119] S2, heat treating the first mixture under an inert atmosphere (300° C., 6 h) to obtain a second mixture;

[0120] The PP bond of the phosphorus element dissociates and forms a new bond with the adjacent tetrahedron P4, thereby transforming into a red phosphorus element similar to a polymer chain structure;

[0121] S3, stirring the second mixture in 3% dilute hydrochloric acid for 4 hours to obtain a third mixture;

[0122] Wherein, the mass ratio of the dilute hydrochloric acid to the second mixture is 50:1;

[0123] wherein the calcium silicate is dissolved by the dilute hydrochloric acid to form a regular pore structure on the hard carbon;

[0124] S4, the third mixture is pulverized in sequence until the average particle size D50 of the particles is 5 μm-6 μm, and then subjected to demagnetization treatment, so as to obtain the phosphorus-carbon composite negative electrode material, and the electron microscopy characterization is as follows: Figure 5 shown.

[0125] In this embodiment, the irregular pore structure is a through hole or a closed hole, more than 99% of the irregular pore structure has a pore size less than 2nm, and less than 1% of the irregular pore structure has a pore size greater than 2nm, which is equivalent to the porous structure in Comparative Example 5;

[0126] The regular hole structure is a through hole, and the pore size of the regular hole structure is nanometer-level or micrometer-level;

[0127] The irregular pore structure and the regular pore structure provide space for the expansion of phosphorus, thereby improving the cycle performance of the phosphorus-carbon composite negative electrode material while maintaining the capacity; at the same time, the contact area between phosphorus and the electrolyte is reduced, so the first efficiency is also improved; in addition, the regular pore structure provides a channel for sodium ions to quickly shuttle, so it has good rate performance.

[0128] Example 2

[0129] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0130] The heat treatment conditions in step S2 are 1.5 GPa, 200° C., and 6 h, so that the phosphorus element is transformed into black phosphorus element by heat;

[0131] Compared with Example 1, black phosphorus has a lamellar structure and high electrical conductivity, so the specific surface area is slightly lower, but on the basis of the porous carbon material, a high electronic conductivity is obtained, so it has a higher rate performance, as shown in Figure 6 As shown in the first cycle charge and discharge curve, the platform area capacity ratio of Example 2 is larger; in addition, the black phosphorus is located in the irregular pore structure and the regular pore structure, so the cycle performance is better.

[0132] Example 3

[0133] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0134] Soft carbon is used in step S1;

[0135] Compared with Example 1, the carbon atoms of the soft carbon are arranged more closely, with fewer defects, less carbon participating in the reaction, less carbon monoxide gas produced, a smaller specific surface area, and fewer irregular pore structures, so the rate performance is slightly worse and the cycle performance is better.

[0136] Example 4

[0137] This embodiment provides a phosphorus-carbon composite negative electrode material, the preparation steps of which include:

[0138] S1, mixing graphite, elemental phosphorus, and silicon dioxide in a molar ratio of 20:1:3 under an inert atmosphere (VC mixer) to obtain a first mixture;

[0139] S2, heat treating the first mixture under an inert atmosphere (300° C., 6 h) to obtain a second mixture;

[0140] The PP bond of the phosphorus element dissociates and forms a new bond with the adjacent tetrahedron P4, thereby transforming into a red phosphorus element similar to a polymer chain structure;

[0141] S3, stirring the second mixture in a 3% sodium hydroxide aqueous solution for 4 hours to obtain a third mixture;

[0142] Wherein, the mass ratio of the sodium hydroxide aqueous solution to the second mixture is 50:1;

[0143] wherein the silicon dioxide is dissolved by sodium hydroxide to form a regular pore structure on the graphite;

[0144] S4, successively pulverizing the third mixture until the average particle size D50 of the particles is 5 μm-6 μm, and performing a demagnetization treatment to obtain the phosphorus-carbon composite negative electrode material.

[0145] Compared with Example 1, the carbon atoms of graphite are closely arranged and basically have no defects, so they are basically unable to participate in the reaction in Example 1, that is, there is no irregular pore structure; however, after mixing graphite, elemental phosphorus, and silicon dioxide, they are converted into red phosphorus in situ, and the silicon dioxide is dissolved in sodium hydroxide, a similar regular pore structure can be formed, such as Figure 7 As shown, the rate performance is poor and the cycle performance is good.

[0146] Example 5

[0147] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0148] In step S1, the molar ratio of hard carbon, calcium phosphate, and silicon dioxide is 20:1:1;

[0149] Compared with Example 1, the molar ratio of silicon dioxide is reduced, so the amount of calcium phosphate participating in the reaction is reduced, and the amount of phosphorus and calcium silicate generated by the reaction is correspondingly reduced, so the output of high-capacity phosphorus is reduced; the amount of phosphorus is relatively reduced under the same mass, and the material capacity is reduced; at the same time, the unreacted calcium phosphate is also dissolved in step S3 to form a regular pore structure; in this way, the material capacity is reduced, and the space provided for the same amount of phosphorus element becomes larger, so the cycle performance is improved; in addition, the channels provided for sodium ion shuttle are reduced, so the rate performance is worse.

[0150] Example 6

[0151] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0152] The molar ratio of hard carbon to calcium phosphate used in step S1 is 200:1;

[0153] Compared with Example 1, the molar ratio of hard carbon is increased, the capacity of the phosphorus-carbon composite negative electrode material changes, the irregular pore structure decreases, and the specific surface area decreases; thus, the constraint on phosphorus is increased, the cycle performance is improved, and the rate performance is reduced.

[0154] Example 7

[0155] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0156] The cooling rate in step S1 is 2°C / min;

[0157] Compared with Example 1, the cooling rate is reduced, and the calcium silicate crystals grow in this process, so that the pore size of the regular pore structure formed in step S3 becomes larger and the specific surface area decreases. Although a larger space is provided for the expansion of phosphorus, the larger specific surface area leads to an excessively large base area with the electrolyte, and the cycle performance becomes worse.

[0158] Example 8

[0159] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0160] The high temperature sintering conditions in step S1 are 1500°C, 2h;

[0161] By increasing the temperature of high-temperature sintering, the time can be shortened, and the same effect as in Example 1 can be achieved.

[0162] Example 9

[0163] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0164] The further mixing in step S1 is performed by ball milling at 200 r / min for 6 h;

[0165] The electron microscopy characterization of the obtained phosphorus-carbon composite negative electrode material is as follows Figure 8 shown.

[0166] Compared with Example 1, the mixing method of the ball mill can trim the surface of the hard carbon, remove the edges and corners, and obtain a more rounded spherical material; in addition, the spherical material has a more uniform stress-bearing angle during the charge and discharge process, so the overall expansion of the material is smaller, showing excellent cycle performance; at the same time, when the spherical material reacts with the electrolyte, the reaction path between the electrolyte ions and the material is shorter, and the rate performance is better.

[0167] Example 10

[0168] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0169] The heat treatment conditions in step S2 are 500°C, 2h;

[0170] By increasing the temperature of the heat treatment, the time can be shortened, and the same effect as in Example 1 can be achieved.

[0171] Embodiment 11

[0172] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0173] Dilute nitric acid is used in step S3;

[0174] The treatment with dilute nitric acid has basically the same effect as that with dilute hydrochloric acid.

[0175] Example 12

[0176] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0177] In step S3, 5% dilute hydrochloric acid is used and the stirring time is 3 hours.

[0178] The concentration of dilute hydrochloric acid is higher, and the calcium silicate is dissolved more thoroughly, so the regular pore structure is slightly more than that of Example 1, and the rate performance is slightly improved.

[0179] Embodiment 13

[0180] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0181] The mass ratio of the dilute hydrochloric acid to the second mixture in step S3 is 30:1;

[0182] In Example 1, Example 11, Example 12, and Example 13, changes in parameters such as the type, concentration, mass ratio, or stirring time of the dilute acid have almost no effect on the performance.

[0183] Embodiment 14

[0184] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0185] The heat treatment conditions in step S2 are 2 GPa, 200°C, 6 h;

[0186] The effect achieved is basically the same as that of Example 2.

[0187] Embodiment 15

[0188] This embodiment provides a phosphorus-carbon composite negative electrode material, and its preparation steps are basically the same as those in Embodiment 1, except that:

[0189] The heat treatment conditions in step S2 are 1 GPa, 400°C, 6 h;

[0190] The effect achieved is basically the same as that of Example 2.

[0191] The performance parameters of Comparative Example 1 to Example 15 are shown in the following table:

[0192]

[0193]

[0194] Among them, the electrode resistance is tested using a four-probe resistance meter.

[0195] In summary, the ratio of carbon material, phosphate, and silicon dioxide in the preparation method of the present invention can regulate the ratio of irregular pore structures, the cooling rate during cooling can regulate the ratio of regular pore structures, and the mixing method of phosphorus element, carbon material, and silicate can regulate the morphology of phosphorus-carbon composite negative electrode materials; thereby effectively solving the problems of small volume constraint effect when depositing elemental phosphorus in a simple porous carbon structure, less depositable phosphorus resulting in lower material capacity, etc., and a high-rate, low-expansion, high-capacity, and long-cycle negative electrode material can be obtained, thereby improving the rate performance, energy density, and cycle performance of the battery to a certain extent, bringing significant economic and social benefits.

[0196] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A phosphorus-carbon composite negative electrode material, comprising: A porous carbon material (1); characterized in that: The porous carbon material (1) has an irregular pore structure (11) and a regular pore structure (12); The irregular pore structure (11) is a through hole or a closed hole, more than 99% of the irregular pore structure (11) has a pore size less than 2 nm, and less than 1% of the irregular pore structure (11) has a pore size greater than 2 nm; Wherein, the regular hole structure (12) is a through hole, and the pore size of the regular hole structure (12) is nanometer-level or micrometer-level; The irregular pore structure (11) and the regular pore structure (12) contain phosphorus (2); Wherein, the phosphorus element (2) is red phosphorus element or black phosphorus element.

2. A method for preparing a phosphorus-carbon composite negative electrode material as claimed in claim 1, characterized in that the steps include: S1, mixing an excess of carbon material, phosphate, and silicon dioxide, and sintering at high temperature so that the carbon material, the phosphate, and the silicon dioxide react to generate carbon monoxide gas, phosphorus vapor, and silicate, and then cooling to obtain a first mixture; Wherein, the excess carbon material partially reacts to generate the carbon monoxide gas to form an irregular pore structure on the remaining carbon material; The phosphorus vapor generated by the reaction solidifies into phosphorus element during the cooling process and is mixed with the remaining carbon material and the silicate generated by the reaction to obtain the first mixture; S2, heat-treating the first mixture to obtain a second mixture; Wherein, the phosphorus element is transformed into red phosphorus element or black phosphorus element by heat; S3, stirring the second mixture in dilute acid to obtain a third mixture; wherein the silicate is dissolved by the dilute acid to form a regular pore structure on the carbon material; S4, sequentially performing a pulverization process and a demagnetization process on the third mixture to obtain the phosphorus-carbon composite negative electrode material.

3. The preparation method according to claim 2, characterized in that: The carbon material is selected from at least one of graphite, hard carbon, soft carbon, or mesophase carbon microspheres; Wherein, the hard carbon is selected from at least one of biomass hard carbon, resin hard carbon, coal-based hard carbon, or petroleum coke / needle coke-based hard carbon.

4. The preparation method according to claim 2, characterized in that: The high-temperature sintering is performed under an inert atmosphere, the temperature of the high-temperature sintering is 1300° C.-1600° C., and the time of the high-temperature sintering is 1 h-4 h.

5. The preparation method according to claim 2, characterized in that: The phosphorus element, the carbon material, and the silicate are further mixed under an inert atmosphere, and the further mixing is at least one of VC mixing, high-speed mixing, or ball milling mixing.

6. The preparation method according to claim 2, characterized in that: The heat treatment is performed under an inert atmosphere, the temperature of the heat treatment is 200° C.-600° C., and the time of the heat treatment is 2 h-8 h.

7. The preparation method according to claim 2, characterized in that: The second mixture is stirred in the dilute acid for 2 hours to 10 hours. The dilute acid is dilute nitric acid or / and dilute hydrochloric acid. The concentration of the dilute acid is 1% to 10%.

8. The preparation method according to claim 2, characterized in that: After the pulverization process, the average particle size D50 of the particles is 5 μm-6 μm.

9. A negative electrode plate, characterized in that: include: The phosphorus-carbon composite negative electrode material as claimed in claim 1.

10. A secondary battery, characterized in that: include: The negative electrode plate as claimed in claim 9.